The Influence of Illustrated Folklore on Elementary School Students' Reading Interests - Mirda Indriani; Otang Kurniaman; Syahrilfuddin Syahrilfuddin (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study intends to evaluate the differences in the increase in reading interest of students who receive learning treatment using illustrated folklore books and students who study using books used in traditional learning. This research employed a quasi-experimental strategy using a matched-pairs control group. The 2022–2023 academic year's odd semester Indonesian language class was the setting for this study. Questions like "what," "who," "where," "when," "why," and "how" are used in the information-gathering material. The subjects in this study were 5th grade students consisting of 5 B and 5 C classes, where 5 C was the experimental class and 5 B was the class control. In this study, data were collected using pre-tests and post-tests given to the experimental class and control class, totaling 25 statement items. As a prerequisite test before testing the hypothesis, normality and homogeneity tests were carried out, which were processed using the SPSS 22 program. Based on the results of the hypothesis testing, a significance value (2-tailed) was obtained of 0.000 0.05 with an average experimental group having an average value of 79 .74 while the control group obtained an average value of 68.95. So that it can be reduced to 14.19%. Thus it can be concluded that there is an influence of pictorial folklore on reading interest of fifth-grade elementary school students.